Foldscope as an Innovative Teaching Tool - Carlos Hernández-Pérez; María Nieto-Sobrino (MDPI AG, 2022)
This study deals with the descriptive analysis of the opinion of a pilot group of students at the University of Salamanca about the use of an innovative origami microscope: the Foldscope. Data were collected from an online satisfaction survey of 92 students of Plant Histology (Degree in Biology) during their laboratory practices. These surveys collected their opinions about the educational effectiveness of an innovative and economic foldable microscope made of paper. The foldscope is easy to use and can be used individually or collectively, thanks to its projection capability. The results show that the participants have a positive impression regarding the use of this tool to study plant structures, and they recommend its use in the years thereafter. In this regard, it is demonstrated that the price of microscopes is no longer a problem for the teaching of some subjects, such as Plant Histology.